g(g(x))= 9x+2

==> g(g(x))= 3(3x+2) + 2

==> g(x)= 3x+2

==> We will check.

**==> g(x)= 3x+2**

==> g(g(x))= g(3x+2)= 3(3x+2) + 2

==> g(g(x))= 9x+6 + 2 = 9x+8

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now